Acceptability of pharmacotherapy for hazardous alcohol use among men who have sex with men: Findings from a qualitative study. (December 2018) - Hsiang, Elaine; Jennings, Danielle; Matheson, Tim; Hern, Jaclyn; Euren, Jason; Santos, Glenn-Milo
Abstract: Introduction: Men who have sex with men (MSM) experience high rates of binge drinking, alcohol use disorder (AUD), and alcohol-related health issues. Pharmacotherapy for AUD can reduce hazardous drinking, yet remains underutilized among MSM. This qualitative study examined knowledge and perceptions regarding AUD medications among MSM, with an emphasis on naltrexone. Methods: Three focus group discussions (FGDs) with MSM who consumed alcohol in the past year were conducted in February 2015 ( N  = 39) in the San Francisco Bay Area. The FGD guide generated discussions about hazardous drinking, the social contexts of drinking, and alcohol reduction and cessation options, including pharmacotherapy. Interviews were analyzed via directed content analysis to codify themes. Results: For participants, drinking at LGBTQ bars was an important social activity. Many expressed interest in reducing alcohol use, but few had heard of pharmacotherapy for AUD. Potential uptake was limited by perceptions of disulfiram as the prototype medication, side effects associated with disulfiram, and concerns that medications do not address alcohol-related stigma or social drivers of drinking. Participants were more receptive to pharmacotherapy when presented with medication options that did not require abstinence. Participants reported being more likely to try pharmacotherapy as part of a peer group or treatment program. Conclusions: Efforts to increase the knowledge and availability of naltrexone and harm reduction approaches, while addressing addiction- and medication-related stigma, might improve pharmacotherapy uptake for AUD and decrease hazardous drinking among MSM for whom alcohol holds social significance. Highlights: For our participants, drinking at LGBTQ bars held social salience. Acceptability of pharmacotherapy was limited by concerns over side effects. Disulfiram was perceived as the prototype medication for alcohol use disorder. Greater visibility of naltrexone and harm reduction approaches may improve uptake.